1998
DOI: 10.1021/ja970577p
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Light-Induced Morphological Change in Langmuir−Blodgett Films

Abstract: An amphiphilic anionic azobenzene derivative, soluble in water, formed a monolayer on an aqueous subphase containing a water-soluble polycation. The monolayers were transferred onto solid substrate by the Langmuir−Blodgett (LB) technique. XPS measurements showed that ion exchange reaction proceeded almost completely at the air−water interface and that the ratio of the monomer unit of the polycation to the azobenzene was almost unity. UV/vis absorption and IR measurements indicated that the azobenzene photoisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 29 publications
3
82
1
1
Order By: Relevance
“…They reported that crystals of p-conjugated compounds with a thiophene-pyrrole-thiophene chemical skeleton produce a gold color 5) . The aggregation of azobenzene derivatives has been extensively studied, and they have been found to form layers of J-aggregates or H-aggregates on solid substrates 6,7) . However, most of these studies were limited to the photoisomerization of several layers consisting of J-or H-aggregates; there are no reports on the color of crystals formed by stacking of a number of monolayers formed from the Jaggregates of an azobenzene derivative.…”
Section: (Nn-dimethylamino)] Ethoxy}azobenzene ( ) (mentioning
confidence: 99%
“…They reported that crystals of p-conjugated compounds with a thiophene-pyrrole-thiophene chemical skeleton produce a gold color 5) . The aggregation of azobenzene derivatives has been extensively studied, and they have been found to form layers of J-aggregates or H-aggregates on solid substrates 6,7) . However, most of these studies were limited to the photoisomerization of several layers consisting of J-or H-aggregates; there are no reports on the color of crystals formed by stacking of a number of monolayers formed from the Jaggregates of an azobenzene derivative.…”
Section: (Nn-dimethylamino)] Ethoxy}azobenzene ( ) (mentioning
confidence: 99%
“…Matsumoto et al 43,44 have prepared LB films consisting of an ion complex formed between an anionic Az derivative and a cationic polymer. A very flat surface in the ion-complex LB monolayer on mica is observed before illumination.…”
Section: Visualization Of Polymer Motions By Microscopic Observationsmentioning
confidence: 99%
“…Arachidic acid is a typical Langmuir-film-forming molecule and forms stable Langmuir films. Because of the attractive electrostatic interactions, Langmuir films of arachidic acid induce the adsorption of cationic molecules 21 and polymers 22 , as well as the crystallization of proteins 23 and inorganic compounds 24 . We avoided these attractive electrostatic interactions because the strong attractive interactions, if present, may dominate the interactions between arachidic acid and the water-soluble surfactants.…”
Section: Introductionmentioning
confidence: 99%